2009
DOI: 10.1007/s10340-009-0258-9
|View full text |Cite
|
Sign up to set email alerts
|

Plant characteristics mediated by growing conditions can impact parasitoid’s ability to attack host aphids in winter canola

Abstract: Winter canola (Brassica napus) is an important crop in various parts of the world. It is planted in fall, vernalized during winter and oVers higher yields than spring canola. One of the key aphid pests of this crop is Myzus persicae Sulzer (Homoptera: Aphididae). Recent surveys in Europe showed that M. persicae in winter canola is parasitized by Aphidius matricariae and Diaeretiella rapae, but not by other aphidiine parasitoid species known to attack M. persicae in other crops. During vernalization, winter can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…A similar program has been implemented with T. achaeae, which is currently used against Tuta absoluta in Europe, despite a parasitism rate of about 50% on this pest . Multiple abiotic and biotic factors can directly affect parasitoid efficiency (Mulatu et al 2006;Emana 2007;Desneux and Ramirez-Romero 2009;Rousse et al 2009) and therefore they should be considered and carefully studied. Difference in important biological traits related to Trichogramma species effectiveness can vary among strains of a same species (Klug and Meyhöfer 2009;Pizzol et al 2010;Tabone et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A similar program has been implemented with T. achaeae, which is currently used against Tuta absoluta in Europe, despite a parasitism rate of about 50% on this pest . Multiple abiotic and biotic factors can directly affect parasitoid efficiency (Mulatu et al 2006;Emana 2007;Desneux and Ramirez-Romero 2009;Rousse et al 2009) and therefore they should be considered and carefully studied. Difference in important biological traits related to Trichogramma species effectiveness can vary among strains of a same species (Klug and Meyhöfer 2009;Pizzol et al 2010;Tabone et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The low population of this aphid on these five cultivars might result in less damage and yield loss. Biotic and abiotic factors in field conditions could be affecting the population density of M. persicae on canola cultivars (Athanassiou et al, 2003;Desneux and Ramirez-Romero, 2009); therefore, we investigated the preferences and performance of M. persicae on Zarfam, RGS003, Opera, Elite, Okapi and Ebonite cultivars under controlled conditions. This study demonstrated that the host preference of M. persicae varied among the tested canola cultivars, and Zarfam was the most preferred, whereas Opera was the least preferred cultivar in terms of attraction.…”
Section: Discussionmentioning
confidence: 99%
“…The slowest development rate and lowest intrinsic rate of the natural increase of M. persicae on Opera would result in a lower population growth that in turn should lead to lower subsequent infestations by this pest. Also, plants responsible for antibiotics may have an indirect effect by increasing the exposure of the insect to its native natural enemies as a result of a prolonged develop-mental time (Desneux and Ramirez-Romero, 2009). Using resistant cultivars has an important role in the IPM of M. persicae in Iran, but the resistance level of Opera cultivar reported in this paper is not sufficient to achieve adequate control of M. persicae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the artificial conditions of this primary screening, parasitoid efficiency waits to be determined under more realistic conditions. Under natural conditions, various factors like crop architecture, plant morphology, prey distribution and climatic conditions could affect the efficiency and behaviour of natural enemies and may affect the efficacy of biological control (Andow and Prokrym 1990;Rutledge et al 2003;Desneux et al 2006;Tabone et al 2006;Carrillo et al 2008;Desneux and O'Neil 2008;Desneux and Ramirez-Romero 2009). For Trichogrammatidae, parasitism levels vary greatly among different habitats, plant species and plant structures, and plant spacing, odour and chemistry all play a role in moulding the efficiency of Trichogramma spp.…”
Section: Introductionmentioning
confidence: 96%